Analgesic and anti-inflammatory effect of Stichopus vastus on animal model - Mohd Faeiz, Pauzi; Siti Norazlina, Juhari (2021)
Chronic pain is a major global health issue. Treating chronic pain is a challenging task as there can be multiple contributing factors for pain. Currently available opioid analgesics therapy is frequently used to treat chronic pain. Although this mode effective in certain cases, opiods may lead to greater health consequences such as misuse or overdose. Thus this study aims to evaluate the analgesic and antiinflammatory effect of Stichopus vastus extract on injury in rats. Stichopus vastus or known as sea cucumber, is marine invertebrate, is used in folk medicine for the treatment of various diseases and disorder. Scientifically shown promising features of anti-inflammatory and analgesics properties as reported by previous literature.